Physico-chemical characteristics and sensory evaluation of Sikkim mandarin wine - Lego, Aina; Upadhyay, Sujata; Bhutia, Karma Diki; Sharma , Laxuman (Journal of Postharvest Technology, 2024)
The present study entitled “Physico-chemical characteristics and sensory evaluation of Sikkim Mandarin wine by using three different types of  Yeast” was carried out at Dept. Of Horticulture, Sikkim University, Gangtok during 2019-2021 with the objectives to study the effect of initial and  final Total Soluble Solids in Sikkim mandarin wine, To study the alcohol content in the Sikkim mandarin wine from initial maturation (0 days) to  final maturation (4 months) and to study the sensory effect of three different types of yeast in prepared Sikkim mandarin wine.The maturation  alcohol content of all the wine increased while TSS decreased during maturation. The fermentation of treated juice, initial sugar concentration  played an important role. The fermentation of efficiency of yeast decreased with increase in the initial sugar concentration and bitterness in  wine was observed. There is a good potential for making wine from Sikkim mandarin fruits since the TSS content of the juice ranges between  10-120Brix. It is recommended to add cane sugar to have suitable alcohol content in the final wine to remove bitterness and also can added  different flavour to have different taste. The result of the present investigation indicated that the wine made from Sikkim mandarin having  Treatment T11 (TSS of 280Brix and SO2 100 ppm), fermentation by Brewer’s Yeast and matured for 4 months had the highest overall sensory  score of 7/10 and having 10.05% ethanol content.
Keywords: Sikkim mandarin; active dry yeast; brewer’s yeast; Marcha (local yeast); wine